Insula Volume and Salience Network Are Associated with Memory Decline in Parkinson Disease: Complementary Analyses of Voxel-Based Morphometry versus Volume of Interest - Yan-Ting Lu; Wen-Neng Chang; Chiung-Chih Chang; Cheng-Hsien Lu; Nai-Ching Chen; Chi-Wei Huang; Wei-Che Lin; Ya-Ting Chang (Parkinson's Disease)
Objective. We investigated structural brain change in subjects with a clinical diagnosis of Parkinson disease with mild cognitive impairment (PD-MCI) and examined its relationship with memory impairment. Methods. Twenty-three PD-MCI patients were enrolled and underwent cognitive evaluation and 3-dimensional T1-weighted imaging. Voxel-based morphometry (VBM) was used to assess brain-behavior correlations and examine the relationship between insula and memory score. VOI methods replicated results obtained from VBM. Results. VBM uncovered the notion that memory scores were positively correlated with the gray matter (GM) density in the insular cortex and a significant positive correlation between overall cognitive performance and concentration of GM within the lateral temporal cortex. In VOI analyses, our results suggested a positive correlation between the insula and composite free-recall verbal memory (ρ=0.617, P=0.003) and the delayed free-recall verbal memory subdomain (ρ=0.725, P<0.001). Furthermore, we found a positive correlation between the insula and caudate (σ=0.570, P=0.006) and putamen volume (σ=0.683, P<0.001). Conclusions. In patients with PD-MCI, atrophic changes in the insula may be related to memory deficits, and the brain-behavior correlation may be associated with atrophic change in the striatum within the salience network.